Plastic scintillators with efficient light output and pulse shape discrimination produced via photoinitiated polymerization. Issue 15 (18th December 2018) - Lim, Allison; Mahl, Adam; Latta, Joseph; Yemam, Henok A.; Greife, Uwe; Sellinger, Alan
ABSTRACT: Poly(vinyl toluene) (PVT) overdoped with 2, 5‐diphenyloxazole and using 1, 4‐bis(5‐phenyloxazol‐2‐yl)benzene as a fluorescent secondary dopant can be used to detect and differentiate neutron and gamma radiation via scintillation. The low cost of PVT makes these plastic scintillators attractive for both portable and larger sized first line detection of special nuclear materials. Current fabrication methods rely on thermally initiated radical polymerization that generally requires an approximately 5‐day heating process in order to produce high quality scintillators. In this work, we report a proof‐of‐concept photopolymerization process to prepare plastic scintillators up to 20 g in size in 1 day. These plastic scintillators were comparable to standard thermally polymerized samples in terms of their physical properties and response to various radiation sources. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47381. Abstract : Plastic scintillators were produced in ∼1 day via photo‐initiated polymerization resulting in materials with efficient neutron and gamma radiation discrimination.